2019
DOI: 10.5385/nm.2019.26.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Nutritional Status at Birth and Need for Respiratory Support on the First Day of Life

Abstract: Purpose: Nutritional markers, such as total protein, albumin, and vitamin D have been reportedly associated with neonatal outcomes. This study aimed to assess the correlation between nutritional markers at birth and the need for respiratory support on the first day of life. Methods: This retrospective study included 94 newborns admitted to the neonatal intensive care unit of Kyungpook National University Children's Hospital between March and December 2017. We measured levels of nutritional markers, including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Moison et al (8) confirmed that compared to well-preterm infants, those with RDS had a lower albumin level. Jang et al (9) retrospectively analyzed the nutritional markers of 94 newborns admitted to the NICU at birth. They observed that the need for respiratory support on the first day of life decreased 0.001-fold for every 1 g/dL increase in albumin (95%CI, 0.000-0.136, P = 0.009) levels and finally proposed that nutritional status at birth was related to the need for respiratory support on the first day after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Moison et al (8) confirmed that compared to well-preterm infants, those with RDS had a lower albumin level. Jang et al (9) retrospectively analyzed the nutritional markers of 94 newborns admitted to the NICU at birth. They observed that the need for respiratory support on the first day of life decreased 0.001-fold for every 1 g/dL increase in albumin (95%CI, 0.000-0.136, P = 0.009) levels and finally proposed that nutritional status at birth was related to the need for respiratory support on the first day after birth.…”
Section: Discussionmentioning
confidence: 99%